KAJIAN TENTANG PERANCANGAN ALAT DAN SISTEM AUTO FOKUS CITRA DENGAN METODE MTF - Gunawan Gunawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Tools and application programs are created is a tool that is integrated with the microscope to capture images of white blood cells automatically with automatically adjust the image focus with the Modulation Transfer Function method and an application to detect and perform recognition on the type of white blood cell using Local Binary Pattern method. Image taken from preparations in the form of images of red blood cells and white blood cells. Based on the results of testing on a microscope auto focus system has been able to run well when capture images automatically with manual verification using human eye can achieve a 100% success rate. Key wordsAuto Focus, Leukocyte, Local Binary Pattern, Modulation Transfer Function, White Blood Cell